Nanostructures of Tungsten Trioxide, Nickel Oxide and Niobium Oxide for Chemical Sensing Applications. (2015) - Bertuna, Angela; Comini, Elisabetta; Kaur, Navpreet; Poli, Nicola; Zappa, Dario; Sberveglieri, Veronica; Sberveglieri, Giorgio
Abstract: Tungsten trioxide nanowires, nickel oxide nanowires and niobium oxide nanostructures weresynthesized by thermal oxidation, vapour-liquid-solid (VLS) technique and hydrothermal method, respectively. Alumina (2 · 2 mm 2 ) substrates were used for growth of the different metal oxidesnanostructures. Thin films of tungsten or niobium are used as source material for WO3 and Nb2 O5 . Anultrathin film of gold was deposited on alumina as catalyst for NiO. All these materials were depositedby RF magnetron sputtering. The morphology was investigated by scanning electron microscope andthe functional properties of these structures were tested towards several gaseous species at differentworking temperatures. The results obtained show that these sensing materials have similarperformances considering the different n- and p-type semiconductors behaviour. Tungstentrioxide (WO3 ) nanowires, nickel oxide (NiO) nanowires and niobium oxide (Nb2 O5 ) nanostructures were synthesized by thermal oxidation, vapor-liquid-solid (VLS) technique and hydrothermal method, respectively. The morphology was investigated by scanning electron microscope and the functional properties of these structures as gas sensors were tested for several gaseous species at different working temperatures. In this work a comparison between the sensitivity of these devices towards acetone is shown.